The role of actors in implementing policies for the protection of child victims of sexual violence in Aceh - Kamal, Saiful; Fauzi, Achmad (Jurnal Anifa: Studi Gender dan Anak, 2023)
Protection of child victims of sexual violence is a very important issue in Aceh, Indonesia. Children, as a vulnerable group, need strong protection and support to overcome the negative impacts that may arise from sexual violence. In this context, many actors implement child protection policies, including the central government, DPR RI, regional governments, and institutions such as the Indonesian Child Protection Commission (KPAI) and the Witness and Victim Protection Agency (LPSK). This research uses a descriptive qualitative approach with literature study methods and online data search. Data analysis techniques involve organizing data, coding, and developing descriptions and themes. It is hoped that the results of this research will provide a better understanding of the role of policy actors in protecting children from sexual violence. This article identifies these actors and describes their role in implementing policies to protect child victims of sexual violence in Aceh. These actors' roles include legislation, supervision, assistance, trauma recovery, legal assistance, motivation, and collaboration between institutions. The analysis results show that cooperation and coordination between these actors is very important to ensure that children who are victims of sexual violence receive comprehensive protection. As awareness of the importance of child protection increases, this article provides a better understanding of how these actors play a role in protecting children in Aceh from sexual violence.